On-load tap changing transformer studies for a small microgrid - Koh, Vesley Yun Rui (Nanyang Technological University, 2023)
The microgrid located in Clean Energy Research Laboratory S2-B7C-05 consists of three On-Load Tap Changing Transformers, a Synchronous Generator, a Programmable Load, an Induction Generator, a Capacitor Bank, etc. The On-Load Tap Changing (OLTC) Transformers are installed between certain nodes of the microgrid to adjust the voltages so as to avoid large voltage drops in the network. The transformers are controlled using a Programmable Logic Controller (PLC) via Modbus TCP/IP protocol. A fault occurred to one of the OLTC Transformers last year. Fault diagnostics and subsequent network restoration are required as soon as possible.